HELLENISM IN ISLAM - Pepen Irpan Fauzan; A Khoirul Fata (IAIN Tulungagung, 2018)
The early Muslim society took much of the scientific treasures from other civilizations, especially from ancient Greek. One of the scientific traditions taken from Greek is Hellenism. Using a historical approach, this article tries to assess the contiguity of Islam with the Hellenism. There are three points will be discussed: When has Islam met to the Hellenism in first time? What are the factors that support the scientific contact between both of the civilizations? To what extent Hellenism influenced the development of scientific tradition in early Muslim community? Our study shows that the Muslims have known the Hellenistic tradition since the 7th century in Ummayyad era, not the 8th century as some scholars claim. Second, there are three factors underlying early Muslim studied Hellenism (1) Support from Qur’anic teachings, (2) The need to argue with both of other Muslim groups and Non-Muslims community, (3) The need of the Caliphs to legitimize their power. Third, when Muslims have known the Hellenism, they did not only adopt the Hellenism ideas, but also provide reviews, critical notes, and further more developed its own scientific tradition combined with the qur’anic teachings.